New Method of Cold Forming by the Spheres for Pipe Converting to the T-shape Tube. (2016) - Faraji, Hossein; Khalili, Khalil
Abstract: In the current paper, finite element simulation for forming C12200 copper alloy and transforming it to T-shaped tube via balls has been done. The main purpose of this paper is to introduce a new cold forming method which is similar to hydroforming having the difference that instead of using fluid, metal and rigid balls have been used to form tube. Simulation results indicated that by decreasing the size of the balls, the rate of stress concentration in tube forming area will be increased and the rate of tube forming will be increased. Therefore, by applying smaller balls, the rate of tube forming can be increased. Also, results obtained from simulations showed that by applying larger balls in the mandrel's edge and smaller balls in forming area, rate of elements' strain and also forming in the forming area will be increased.